2005
DOI: 10.1179/136485905x51373
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology ofToxocara canisinfection among aboriginal schoolchildren in the mountainous areas of north–eastern Taiwan

Abstract: A sero-epidemiological study of Toxocara canis infection was conducted among Atayal schoolchildren (aged 7-12 years) residing in the mountainous areas of north-eastern Taiwan. The 73 children investigated were each checked for anti-Toxocara IgG, in ELISA based on the larval excretory-secretory antigens of T. canis larvae. A short, self-administered questionnaire was then used to collect relevant information from each subject, including data on the keeping of dogs, playing in soil, eating raw vegetables, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
3
16
2
3
Order By: Relevance
“…[32][33][34] Young age, 35 low socioeconomic status, 36 low parental education, 34,37 and poor sanitation 6 are additional factors contributing to Toxocara exposure in some communities. Dog ownership has been identified as a risk factor in several 11,27,35,[37][38][39] although not all 40 studies of urban and rural populations. None of these known risk factors, except for young age, was significantly associated with Toxocara exposure in our population (P values between 0.338 and 0.921 in multivariate models).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Young age, 35 low socioeconomic status, 36 low parental education, 34,37 and poor sanitation 6 are additional factors contributing to Toxocara exposure in some communities. Dog ownership has been identified as a risk factor in several 11,27,35,[37][38][39] although not all 40 studies of urban and rural populations. None of these known risk factors, except for young age, was significantly associated with Toxocara exposure in our population (P values between 0.338 and 0.921 in multivariate models).…”
Section: Discussionmentioning
confidence: 99%
“…O fato de possuir cão na casa foi um fator de risco para sorologia positiva em vários estudos 17,19,20,23,24,30,31,[34][35][36] . Alguns autores não encontraram associação entre os donos de cães 17 e a frequência de infecção por Toxocara, o que poderia ser explicado pelas medidas de higiene adequadas adotadas pelos adultos.…”
Section: Epidemiologiaunclassified
“…Em outros estudos brasileiros, a idade prevalente foi acima de 5 anos 13,31,33,55 . Em estudos caso-controle, não foi encontrada diferença significativa em relação à idade 17,29,33,[35][36][37]58 .…”
Section: Epidemiologiaunclassified
See 1 more Smart Citation
“…33 The presence of a dog in the house was a risk factor for seropositivity in several studies. 17,19,20,23,24,30,31,[34][35][36] Some authors have found no association between dog owners 17 and frequency of Toxocara infection, which could be explained by appropriate hygiene measures taken by adults. Other studies have shown an association between positive serology for T. canis in owners of pups under 3 months.…”
mentioning
confidence: 99%